Pengukuran Kesejahteraan Masyarakat Melalui Kinerja Keuangan Daerah Terhadap Indeks Pembangunan Manusia di Kabupaten Aceh Timur - Yulina Astuti; Krisniawati Krisniawati; Muhammad Zulkarnain; Arfriani Maifizar (Prodi Sosiologi FISIP Universitas Teuku Umar, 2019)
The study was conducted with the aim to determine the effect of financial performance consisting of the ratio of independence, efficiency ratio and effectiveness ratio to the Human Development Index. The data used was obtained from the Central Statistics Agency and the Directorate General of Fiscal Balance (DJPK) of the Ministry of Finance of the Republic of Indonesia. Methods of data analysis using multiple linear regression equations, coefficient of determination test (R2) and statistical tests (t test or partial test and F test or simultaneous test). The results showed that 51.7% independence ratio, efficiency ratio and effectiveness ratio influenced the Human Development Index in East Aceh District and 48.3% were influenced by other variables not included in the estimation of this study. Then the independence ratio has a positive but not significant effect on the Human Development Index. The efficiency ratio has a positive but not significant effect on the Human Development Index. The effectiveness ratio has a positive but not significant effect on the Human Development Index. F test results note that simultaneous independence ratios, efficiency ratios and effectiveness ratios have a significant effect on the Human Development Index in East Aceh District. Keywords: Regional Financial Performance, Human Development Index.